2016
DOI: 10.1007/s11883-016-0564-7
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Mimetics: the Past, Current Status and Future Challenges

Abstract: The association between thyroid hormone status and plasma levels of low-density lipoprotein cholesterol has raised the awareness for the development of thyroid hormone mimetics as lipid-lowering agents. The discovery of the two main types of thyroid hormone receptors (α and β) as well as the development of novel combinatorial chemistry providing organ specificity has drastically improved the selectivity of these compounds. In the past decades, several thyroid hormone mimetics have been investigated with the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 51 publications
(61 reference statements)
0
24
0
Order By: Relevance
“…As they activate, HSCs induce mutual changes in D1 and D3 hepatic expression, especially in D3, which diminishes the active-THs accumulation. These mechanisms can cross-talk in their way to affect TH expression [ 103 ]. Putative evidence is needed to elucidate the exact mechanism behind D1–D3 hepatic repair and the control behind TH homeostasis.…”
Section: Immunopathogenesismentioning
confidence: 99%
“…As they activate, HSCs induce mutual changes in D1 and D3 hepatic expression, especially in D3, which diminishes the active-THs accumulation. These mechanisms can cross-talk in their way to affect TH expression [ 103 ]. Putative evidence is needed to elucidate the exact mechanism behind D1–D3 hepatic repair and the control behind TH homeostasis.…”
Section: Immunopathogenesismentioning
confidence: 99%
“…Conversely, hyperthyroidism (excess of thyroid hormone), promotes a hypermetabolic state characterized by increased energy expenditure and weight loss [ 40 ]. These beneficial effects of TH have led to the development of selective thyroid hormone mimetics as powerful new tools against atherosclerosis and obesity [ 41 , 42 ]. Moreover, the role of TH has been demonstrated particularly in glucose homeostasis [ 43 ].…”
Section: Effects Of Th On Central Metabolismmentioning
confidence: 99%
“…However, the thyromimetic eprotirome that has been studied in a phase III clinical trial showed the ability to induce liver injury. 46 Moreover, these drugs likely induce a hypercoagulable state since these drugs specifically stimulate TRβ, and thyroid hormone influences coagulation parameters through this receptor. 47…”
Section: Effects Of Thyroid Hormone On Lipids and The Development Of mentioning
confidence: 99%